IMF Survey, Volume 30, Issue 06. (IMF Survey; IMF Survey ;, 2001)
On March 1, IMF Managing Director Horst Kohler announced the establishment of the International Capital Markets Department in the IMF. Below are edited excerpts from a March 2 press briefing by Kohler and First Deputy Managing Director Stanley Fischer on that decision and on the IMF's response to financial crises, including Turkey (www.imf.org/imfsurvey).